Very early and early neurophysiological abnormalities in Guillain–Barré syndrome: A 4‐year retrospective study. (27th July 2021) - Rasera, Andrea; Romito, Silvia; Segatti, Alessia; Concon, Elisa; Alessandrini, Luca; Basaldella, Federica; Badari, Andrea; Bonetti, Bruno; Squintani, Giovanna
Abstract: Background and purpose: In its initial stages, Guillain–Barré syndrome (GBS) is difficult to identify, because diagnostic criteria may not always be fulfilled. With this retrospective study, we wanted to identify the most common electrophysiological abnormalities seen on neurophysiological examination of GBS patients and its variants in the early phases. Methods: We reviewed the clinical records of patients admitted to our Neurology Unit with a confirmed diagnosis of GBS. The study sample was divided in two subgroups according to whether the neurophysiological examination was performed: within 7 days (very early group) or within 7–15 days (early group). H reflex, F waves, and motor and sensory conduction parameters were judged abnormal if they were outside the normal range for at least two nerves. We evaluated neurophysiological findings in Miller–Fisher syndrome (MFS) separately. Results: The study sample comprised 36 patients. In GBS, the most frequent abnormal neurophysiological parameter was the bilateral absence of the H reflex, followed by F wave abnormalities. Motor conduction parameters were altered in less than 50% of patients, and even less common were sensory nerve action potential reduction and the "sural‐sparing" pattern. In MFS, H reflex was absent bilaterally in 100% of patients, followed by a predominant peripheral sensory involvement, whereas motor conduction parameters were frequently normal. Conclusions: Bilateral absence of the H reflex is the most sensitive parameter in early diagnosis of GBS and its variants. Abstract : Electrodiagnostic findings in GBS and MFS patients: percentage of patients with abnormal results in at least two nerves. When patients were excluded due to the lack of CMAPs, SNAPs or normal sural nerve SNAP, frequencies are calculated based on the number of patients reported in brackets. MCV: motor conduction velocity. DML: distal motor latency. CMAP Dur: compound motor action potential duration. CMAP A: compound motor action potential amplitude. SNAP A: sensory nerve action potential amplitude. SCV: sensory conduction velocity.